Influence of Gender on Environmental Attitude among school students - Mathura, U.; Piratheeban, K. (Jaffna Science Association, 2024)
Environmental education was introduced into Sri Lanka’s curriculum as a coordinated concept to serve as a tool for sustainable development. Research revealed that gender has impacts on environmental attitudes of students in other countries. Therefore, this paper is designed to determine the influence of gender of secondary-level students of Sri Lanka on their environmental attitudes. This research is designed as a quantitative study. 285 samples were selected (total population=1078) through stratified random sampling techniques. Questionnaire consists of fifteen Likert-type questions under three dimensions; Usage of non-biodegradable items (BioD), Eco-friendly behavior (EF) and Conservation of resources (CR), were adapted from Ugulu & Sahin (2013) and Kaiser et al. (1999) and modified as per Sri Lankan context (α=.749). Collected data was analyzed using Chi-Square test and Mann-Whitney U Test. Out of fifteen variables, attitudes towards reading environmental-related articles and news while reading the newspaper (P=.017) and switching off lights when leaving the room (P=.024) showed significant differences based on gender in chi-square test. However, none of the dimension has significant differences with gender of the students in Mann-Whitney U test (p=>.05). Therefore, there are no significant differences between three dimensions and gender of the students. Considering the findings, further studies should be done to study whether only the curriculum or other internal and external factors except gender affect the environmental attitudes of the students. In this way, more concerns could be given in the curriculum revision in order to display more positive attitudes towards the environment.
Keywords: Environment; Gender; Environmental attitude; Secondary-level student; Eco-friendly attitude